Wood - An Inestimable Valuable Good in the Traditional Romanian Household - Magdalena-Cristina Stanciu; Carmen-Alice Teacă (BioResources)
Objects made of wood form one of the most important chapters of the heritage of civilization, culture, and traditional popular art of woodcraft among the Romanian people, encompassing creations that continue to develop this millennia-old legacy. Popular art in wood is, undoubtedly, an organic art. It is deeply connected to work and life in which various objects seamlessly blend utility with beauty in the most natural way possible, fully addressing this dual necessity. Wood art is not just a craft of shapes and motifs; it reveals, in specific stylistic structures, a genuine thought and conception of the world and life.